Perbandingan Persentase Lemak Tubuh Sebelum dan Setelah Melakukan Senam Zumba pada Wanita Dewasa - Tendean, Brigitta A.; Pangemanan, Damajanty H. C.; Sapulete, Ivonny M. (e-Biomedik, 2018)
Abstract: Physical activity is a body movement produced by skeletal muscles which requires energy. Lack of physical activity has a negative impact, one of which is an increase in body fat percentage above the normal threshold or often associated with obesity. Zumba is one of the popular aerobic exercises in the form of dancing. This study was aimed to compare the percentage of body fat before and after undertaking Zumba exercise in adult woman. This was an experimental field study with the one group pretest-posttest design. Samples were obtained by using total sampling technique. Zumba exercise was undertaken for 4 weeks, 3 times a week for 60 minutes. The percentage of body fat was measured by using an instrument based on Bioelectrical Impedance Analysis. Data were analyzed with the Wilcoxon Signed Rank test. The results showed that l6 subjects were involved in this study. The mean percentage of body fat percentage before Zumba exercise was 39.300% (SD±8.1041) meanwhile the mean percentage of body fat percentage after Zumba exercise was 39.031% (SD±7.9232). The statistical analysis to compare the body fat percentage before and after doing Zumba exercise obtained a P value of 0.065. Conclusion: There was no significant difference in body fat percentage before and after undertaking 4-week Zumba exercise among adult females.Keywords: body fat percentage, Zumba exercise Abstrak: Aktivitas fisik merupakan gerakan tubuh yang dihasilkan otot rangka yang memer-lukan energi. Kurangnya aktivitas fisik seperti olahraga memiliki dampak negatif, salah satunya peningkatan persentase lemak tubuh di atas ambang normal atau obesitas. Olahraga yang sedang popular belakangan ini ialah senam Zumba, yaitu latihan aerobik dalam bentuk tarian. Penelitian ini bertujuan untuk mengetahui perbandingan persentase lemak tubuh sebelum dan setelah melakukan senam zumba pada wanita dewasa. Jenis penelitian ialah eksperimental lapangan dengan desain one group pretest-posttest. Teknik sampling yang digunakan ialah total sampling. Senam Zumba dilakukan selama 4 minggu dengan frekuensi 3 kali seminggu yang berdurasi 60 menit. Persentase lemak tubuh diukur menggunakan alat berbasis bioelectrical impedance analysis. Data penelitian dianalisis dengan uji Wilcoxon Signed Rank Test. Hasil penelitian mendapatkan 16 subjek. Rerata persentase lemak tubuh sebelum senam Zumba yaitu 39,300% (SD±8,1041). Rerata persentase lemak tubuh setelah senam Zumba yaitu 39,031% (SD±7,9232). Hasil uji perbandingan persentase lemak tubuh sebelum dan setelah melakukan senam zumba menunjukkan nilai P=0,065. Simpulan: Tidak terdapat perbedaan bermakna dari persentase lemak tubuh sebelum dan setelah melakukan senam zumba selama 4 minggu pada wanita dewasa.Kata kunci: persentase lemak tubuh, senam Zumba